RELIGIOUS MODERATION IN THE ACADEMIC ENVIRONMENT: A STUDY OF INTERNALISATION OF RELIGIOUS VALUES AND PATRIOTISM AT UNIVERSITAS LAMBUNG MANGKURAT - Husin, Gt. Muhammad Irhamna; Rusli, Rusdi; Arief, Muhammad Ihsanul; Ainah, Noor (Psikis : Jurnal Psikologi Islami, 2023)
We are now facing a tsunami wave of social media development. Anyone and anywhere can access religious information. The impact of this correlates with the vital flow of globalization to all levels of society. The negative influence from the media development side gives a strong impetus for social insecurity. Our integrity as citizens will be at stake because of the appeal of social media. To maintain this, it is essential to strengthen and foster so as not to get out of the path of the nation's ideals. This research discusses how students establish relationships with God and each other in the frame of love for the homeland, surrounded by a plurality of religions, tribes, ethnicities, and cultures, to create an attitude of religious moderation. This type of research is included in field research with quantitative and qualitative approaches. Internalization of spiritual values and love for the homeland in students showed positive results. The results of respondent data show that the strong tendency of religious influence has a positive impact and correlates with love for the homeland. Based on the data, 60% strongly agree, and 28% agree with maintaining relationships with others regardless of anything. This reflects that students' religious understanding has shown an inclusive category, which means they can openly accept differences irrespective of religion, ethnicity, and culture, which is necessary in the Republic of Indonesia.